Energy-dependent path of dissipation in nanomechanical resonators - Guttinger, Johannes; Noury, Adrien; Weber, Peter; Eriksson, Axel Martin; Lagoin, Camille; Moser, Joel; Wallraff, Andreas; Isacsson, Andreas; Bachtold, Adrian; Eichler, Christopher (Nature Nanotechnology, 2017)
Energy decay plays a central role in a wide range of phenomena, such as optical emission, nuclear fission, and dissipation in quantum systems. Energy decay is usually described as a system leaking energy irreversibly into an environmental bath. Here, we report on energy decay measurements in nanomechanical systems based on multilayer graphene that cannot be explained by the paradigm of a system directly coupled to a bath. As the energy of a vibrational mode freely decays, the rate of energy decay changes abruptly to a lower value. This finding can be explained by a model where the measured mode hybridizes with other modes of the resonator at high energy. Below a threshold energy, modes are decoupled, resulting in comparatively low decay rates and giant quality factors exceeding 1 million. Our work opens up new possibilities to manipulate vibrational states, engineer hybrid states with mechanical modes at completely different frequencies, and to study the collective motion of this highly tunable system.
CRIS-Team Scopus Importer:2022-06-27